2018
DOI: 10.1007/s40120-018-0111-2
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzazepine Agents in Epilepsy: How Does Eslicarbazepine Acetate Differ?

Abstract: Carbamazepine (CBZ), oxcarbazepine (OXC), and eslicarbazepine acetate (ESL) belong to the dibenzazepine family of antiepileptic drugs and are all thought to primarily act as sodium channel blockers (SCBs). However, ESL is structurally distinct from CBZ and OXC, resulting in differences in metabolism, pharmacokinetics, and pharmacodynamics. Despite a lack of direct comparative data, evidence for potential differences in effectiveness and tolerability within the dibenzazepine family has emerged from studies in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 41 publications
(116 reference statements)
1
45
0
Order By: Relevance
“…Studies conducted primarily in the clinical practice setting have demonstrated that ESL monotherapy can be effective in patients who have transitioned from CBZ monotherapy due to lack of efficacy or poor tolerability. 23 The current study demonstrated that ESL monotherapy maintained seizure control in the majority of patients who transitioned from CBZ-CR to ESL, but the higher risk of seizures observed in the CBZ-CR/ESL group during the first 3-4 months, compared with the ESL/ESL group, illustrates the challenges associated with switching patients from one ASM to another. Published guidance has highlighted that transitioning patients from CBZ to ESL requires careful consideration on a patient-by-patient basis, primarily because CBZ may have a different mechanism of action than ESL [24][25][26] and is a stronger inducer of cytochrome P450 enzymes.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Studies conducted primarily in the clinical practice setting have demonstrated that ESL monotherapy can be effective in patients who have transitioned from CBZ monotherapy due to lack of efficacy or poor tolerability. 23 The current study demonstrated that ESL monotherapy maintained seizure control in the majority of patients who transitioned from CBZ-CR to ESL, but the higher risk of seizures observed in the CBZ-CR/ESL group during the first 3-4 months, compared with the ESL/ESL group, illustrates the challenges associated with switching patients from one ASM to another. Published guidance has highlighted that transitioning patients from CBZ to ESL requires careful consideration on a patient-by-patient basis, primarily because CBZ may have a different mechanism of action than ESL [24][25][26] and is a stronger inducer of cytochrome P450 enzymes.…”
Section: Discussionmentioning
confidence: 58%
“…Studies conducted primarily in the clinical practice setting have demonstrated that ESL monotherapy can be effective in patients who have transitioned from CBZ monotherapy due to lack of efficacy or poor tolerability 23 . The current study demonstrated that ESL monotherapy maintained seizure control in the majority of patients who transitioned from CBZ‐CR to ESL, but the higher risk of seizures observed in the CBZ‐CR/ESL group during the first 3‐4 months, compared with the ESL/ESL group, illustrates the challenges associated with switching patients from one ASM to another.…”
Section: Discussionmentioning
confidence: 99%
“…CBZ is commonly associated with increased serum lipid levels, and there is potential for severe rebound seizures with both CBZ and OXC when adherence is low. 3,4 A key difference between ESL and CBZ is the pharmacokinetic profile and metabolism which conveys real clinical utility. Eslicarbazepine acetate has high bioavailability reaching peak concentration within 2-3 hours, with a significantly longer half-life of 20-24 hours (depending on population studied).…”
Section: Eslicarbazepine Acetatementioning
confidence: 99%
“…CBZ specifically has major potential for significant drug to drug interactions. CBZ is commonly associated with increased serum lipid levels, and there is potential for severe rebound seizures with both CBZ and OXC when adherence is low 3,4 . A key difference between ESL and CBZ is the pharmacokinetic profile and metabolism which conveys real clinical utility.…”
Section: Introductionmentioning
confidence: 99%
“…Eslicarbazepine acetate (ESL) is a voltage‐gated sodium channel blocker antiepileptic drug that belongs to the dibenzazepine family. However, compared to carbamazepine and oxcarbazepine, also members of the same family, ESL has a variety of advantages that include better metabolic and tolerability profiles, lower risk of allergic reactions, and drug interactions . Additional properties of ESL such as its simple titration schedule and the possibility of once‐daily dosing make it a suitable option for monotherapy treatment in patients with focal epilepsy.…”
Section: Introductionmentioning
confidence: 99%